A note on the mechanism of resistance to anoxia and ischaemia in pathophysiological mammalian myelinated nerve. - Ritchie, J M (1985)
Computer simulation of the action potential in myelinated nerve fibres show that the metabolic cost of conduction of an impulse is less than normal in a slightly depolarised fibre. This would account, at least in part, for the greater resistance to ischaemia and anoxia of nerves from diabetics and other pathophysiological conditions.